Durable Donor Hematopoetic Stem Cell Chimerism is Associated with Protection from Native Renal Disease Recurrence in Recipients of Combined Stem Cell/Kidney Transplants. (July 2018) - Ildstad, Suzanne; Leventhal, Joseph; Galvin, John; Gallon, Lorenzo; Stare, Dianne
Abstract : Recurrence of the original cause of ESRD has been observed in standard of care renal transplants and in several ongoing trials of tolerance induction in kidney transplant recipients where donor derived HSC have been deployed to effect donor specific immunomodulation. A common feature of these trials has been the establishment of transient chimerism in the majority of subjects. Since 2009 we have conducted a Phase 2 trial of combined stem cell/living donor kidney transplantation in mismatched and unrelated subjects where the stated goal has been the establishment of durable donor macrochimerism. We have hypothesized that durable chimerism will protect against native ESRD recurrence. Our protocol is based upon tolerogenic CD8+/TCR-facilitating cells (FCRx) and 200 cGy TBI-based nonmyeloablative conditioning. Recipients were conditioned with fludarabine (30mg/m2/dose, days -5, -4, -3), cyclophosphamide (50mg/kg/dose, day-3 and+3), 200 cGy TBI (day-1) followed by a living donor KTx (day0). A G-CSF mobilized peripheral blood mononuclear cell product was apheresed from the donor >2 weeks pre-KTx, processed to remove graft-versus-host disease (GVHD)-producing cells yet retain CD34 + cells and FC, and cryopreserved until administration day+1 post-KTx. 36 subjects have reached at least 1 year of follow up (range 12-105 months) and are the focus of this analysis. Subjects ranged in age from 18-65 years and were from 6/6 HLA matched related to 0/6 matched unrelated. 16 subjects had unrelated and 20 had related donors. Two subjects were re-transplants. MMF and tacrolimus-based immunosuppression (IS) was weaned and discontinued at 1 year if chimerism, normal renal fcn and normal KTx biopsy were noted. 12 subjects in our trial had a cause of ESRD associated with disease recurrence post-TX (6 IgAN, 2 FSGS, 2 Membranous GN, 2 Alport's). Rates of recurrence for these conditions following SOC KTx range from 20% to 60%. 7/12 subjects had durable chimerism established allowing for full withdrawal of IS; none of these subjects, including the two subjects with FSGS, experienced disease recurrence. 3/12 subjects had transient chimerism; 1 subject with Membranous GN developed disease recurrence which was successfully treated with rituximab. 2/12 subjects failed to establish any donor chimerism; 1 of these subjects with IgAN experienced disease recurrence and was successfully treated with corticosteroids. There were no graft losses or patient deaths in this patient subgroup (n=12). Renal function (eGFR) has been excellent (eGFR range 56-102 ml/min overall). In conclusion, the establishment of durable chimerism using our FCRx approach is associated with protection from recurrence of original ESRD. The FCRx approach may be particularly suited for patients at high risk for disease recurrence post-Tx, such as FSGS.